Entre jalecos e togas: a formação profissional de médicos e juristas e os entraves para a efetivação do acesso à saúde no Brasil - Freire Neto, Lourenço de Miranda (2015)
The Theory of Human and Fundamental Rights, now developed and proclaimed in the world of law, particularly after the break with legal positivism and entry at a time said post-positivist, still lacks enough reflection. Thus, we analyzed the phenomenon of a constitution, including a study of a novel Brazilian Constitution of 1988, addressing important issues inherent in their realization. In this way, we seek to build a Theory of Human Rights and Fundamental more pragmatic, that is, focused on solving the offenses basic rights such as access to health care. In this context, we confront the positively valued health guaranteed access to the public health dilemmas in Brazil, through a review of our health system, comparatively with the Health Systems in the World, in order to determine problems and seek solutions. Similarly, an effective instrument for the execution of guarantees such as access to health, it is sometimes innocuous, why we also write about ensuring access to justice, with a contextualized study of the judicialization of health, trying thus to detect problems and give solutions. From this, we find a common obstacle to the effectiveness of this guarantee: the current model of professional training of doctors and lawyers, which is why we end this study with a reflection on our teaching, on interference by the consumer society in education and the discrepancy between social needs in health and justice and the medical and legal training.